Who Reaches the Top? Investigating Gender-Based Performance and Maximum Score Gaps in University Entrance Exams - Hermina Disnawati; Siti Irene Astuti Dwiningrum; Yohanis Ndapa Deda; Salman Rashid; Mariano Dos Santos (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Disparities in the academic readiness of first-year university students remain evident, continuing to challenge higher education systems, particularly when entrance assessments fail to reflect foundational competencies accurately. This study investigates whether gender-based differences exist in entrance exam performance and analyzes students' maximum scores to assess peak academic achievement in two core domains: English proficiency and Quantitative Knowledge. The research was conducted at a public university in East Nusa Tenggara, Indonesia, involving 1,186 students admitted through the independent selection pathway. A comparative quantitative approach was applied using descriptive statistics, Welch’s t-test, and boxplot visualizations in JASP 0.18.3 software. The results showed no statistically significant gender differences in either domain (English: p = 0.504, d = 0.040; Quantitative: p = 0.543, d = –0.036), with nearly identical mean scores and score variability. However, the maximum scores of 17/20 in English and 13/20 in Quantitative Knowledge were far below the full mark, indicating systemic gaps in academic preparedness and possible ceiling effects in test design. These findings support the need to redesign entrance assessments using Item Response Theory (IRT) and to implement bridging or matriculation programs. These interventions can help universities and policymakers ensure fairer and inclusive pathways to promote equitable access and success in higher education.